Review of The Concept of Intercession of The Qur'an on The Day of Judgement - Zuhri, Ahmad (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
The word "syafa’a" (intercession) refers to Allah SWT's generous display of grace in the form of assistance. Intercession on the last day is the most expected part of every human being. Specifically, giving intercession can be analogized as a request to get good and avoid evil. One of the classifications of intercession on the Day of Judgement is intercession. The group of people who get this intercession are people who have a heart that is firmly attached to the Al-Qur'an, making the Al-Qur'an a guide, leader, and guide in their lives. The review of the concept of intercession in the Qur'an given by Allah SWT will be analysed using a descriptive qualitative approach based on several literatures, laws, and opinions of the scholars. The data used in this research refers to the hadith of the Prophet, quotations from Al-Quran verses, and reviews of the opinions of scholars who are oriented towards the intercession of the Qur'an. The results of the research show that intercession in the Qur'an is a gift from Allah, and only He has the full power to give intercession to whoever He wants. Syafa'at is not an absolute guarantee or an opportunity to commit sins, but is a mercy from Allah that can benefit those who are pleased with Him.